LEADERSHIP ON EMPLOYEES’ PERFORMANCE TERANG UTAMA ABADI LTD. THROUGH SENSE OF ACHIEVEMENT - Christian, Davy; Melinda, Tina (TRIKONOMIKA, 2018)
Achievement earned by the company is inseparable from the employees’ performance. There are several factors affecting their performance. Two of them are leadership and motivation. The study aims to examine the influence of leadership on the sense of the achievement of the employees of Terang Utama Abadi (TUA) Ltd., the influence of leadership on the performance of the employees at TUA Ltd., the influence of the sense of achievement on the performance of employees at TUA Ltd., and the sense of achievement as an intervening variable on employee at TUA Ltd.. The respondents of this study were fifty-eight employees at TUA Ltd. This study was a quantitative research with structural equation modelling partial least square method. Questionnaires were used to collect the primary data. This study found that leadership and sense of achievement has positive influence on the employees’ performance. Meanwhile, the sense of achievement served as an intervening variable.